DISEÑO DE UN SISTEMA CONTABLE EN LA BOUTIQUE NIKEL DE LA CIUDAD DE LOJA. PERIODO 01 DE ENERO AL 30 DE JUNIO DEL 2015 - CRUZ GORDILLO, ANDREA JUDITH (2016)
This research paper entitled "DESIGN OF AN ACCOUNTING SYSTEM IN THE NIKEL BOUTIQUE OF THE LOJA CITY. PERIOD 01 JANUARY TO 30 JUNE OF 2015 " is aimed at proposing an accounting system that allows its owner to know the economic situation - real financial company, the same as was done by executing each of the objectives proposed specific: To fulfill the first objective, which states: Taking Inventory of assets, rights and obligations where a general knowledge of the heritage which the company currently has; we proceeded to perform a physical count of each of the items and values that owns the business. For the second objective which is: Develop a chart of accounts that allows the personification of operations generated by the company management by facilitating their identification code; It was necessary to take the initial inventory information to determine the financial accounts and codes to be used, adjusted to the need and nature of business. The third goal relates to: Establish a Manual of Auditors to present in detail the movement of each of the ledger accounts and serve as a guide for efficient and timely registration thereof; It was accomplished through a thorough explanation of each of the accounts that make up the chart of accounts. To fulfill the fourth objective that says Apply Multiple Account 7 System help control the goods account for the generation of accurate and reliable; accounts accounting system only requires registration of purchase and sale was used. Also to run the fifth objective relates to: Develop an accounting recording process in an orderly and systematic daily operations of the company; was necessary to make an initial inventory, to the initial situation, Daybook, Ledger, Trial Balance, Worksheet and Financial Statements such as the state of economic situation, the statement of financial position and the cash flow statement . On the other hand indicates the sixth objective: Apply Financial Indicators to meet liquidity, activity, profitability and debt of the business; It was met through the application of formulas relating the information reflected in the financial statements. The observation, interview and literature review: the methodology used within the scientific method making use of other methods such as the deductive, inductive, descriptive, analytical, synthetic and Mathematics and techniques as applied research. All results Accounting Process whose financial statements reflect the results to June 30, 2015. In the State Economic situation presents a value of $ 41,067.79 Sales and Cost of Sales of $ 25,346.49 which the difference occurs resulting in gross profit on sales of $ 15,721.30 that after deducting expenses and distributions of $ 11,470.57 and $ 637.61 8 respectively Net Income of $ 3,613.12, unfavorable profit for the company because it does not compensate was obtained investment. In the structure of the statement of financial position it was found that the total assets has a value of $ 64,414.50 revealing that the business has sufficient resources to the development of its business; It has a $ 3,695.10 Total liabilities and equity of $ 60,719.40; It is indicating that the company has little dependence of its creditors. The application of financial indicators of liquidity, activity, indebtedness and profitability facilitated to know the economic situation - financial company. Their results showed the following shortcomings: inventory turnover shows that the business makes their goods in cash or accounts receivable after about 173 days because there are some items that have been slow-moving. Accounts Receivable rotate after 128 days because the debts do not recover in time, which leads to lack of cash availability. And Net Profit Margin was 8.80%, which is not very beneficial because it has not come to get a sizable profit on sales made. Finally, the Conclusions and Recommendations of the whole thesis is presented to the Managing Owner considered as an option in taking corrective measures which support business progress.